Three-dimensional coupled design for runner blades and guide vanes of tubular turbine based on bidirectional flow control. Issue 1 (June 2021) - Ji, Qingfeng; Liao, Weili; Jia, XIN; Fan, Honggang
Abstract: Tidal energy is one of the renewable energy resources in the ocean. The tide-power station can supply more continuous electricity if it produces electricity in rising tide and receding tide, which is conductive to the stable operation of power grids. So it is important that the tubular turbine can operate in both directions with higher efficiency in tide-power stations. A full three-dimensional coupled design model for tubular runner blades and guide vanes is established to take full account of the mutual influence of flow between the distributor and runner. Since the simultaneous governing equations are solved in the flow domain including both blades, the coupled performance matches further. The weighted design method for reversible runner blade is presented based on the bidirectional flow information. The designed blade is fit to operate in both directions, which combined characteristics of the two blades working nicely in the positive and negative direction respectively. The reasonable control on the comprehensive performance of reversible blades is realized by selecting the weighted coefficient flexibly.